Improving the Nutrient Absorption and Yield of Chickpeas (Cicer arietinum) and Barley (Hordeum vulgare) under Row Inter-cropping with Foliar Application of Plant Growth Regulators in Saline Soil Conditions - A Talebi; M. R Owji; F Mohajeri; M. R Baziar (پژوهشهای زراعی ایران, 2025)
IntroductionSoil salinity is one of the environmental stresses that is an important threat to agricultural production in the world. The global scientific community has been testing possible technologies for increasing salt stress tolerance in plants for more than three decades. New advances and perspectives have been obtained to restore the productivity of plants under salt stress. Utilization of plant growth regulators is one of the promising strategies to overcome the adverse effects of salinity. Also, row inter-cropping can increase the efficiency of the used resources. Improving the yield of chickpeas and barley in row inter-cropping using foliar spraying of salicylic acid, jasmonic acid and brassinosteroid was the hypothesis proposed in this research. Therefore, the aim of this study was to investigate the effect of these hormones’ application in mixed cropping of chickpeas and barley under salt stress conditions. Materials and MethodsA split plot experiment was conducted in the form of a randomized complete block design with three replications during the growing seasons of 2021 and 2022. This research was carried out in Fasa, Iran. The main factor was the planting arrangement included monocropping of chickpeas and barley and their row inter-cropping (75% chickpeas + 25% barley, 50% chickpeas + 50% barley and 25% chickpeas + 75% barley as row intercrop). The second factor was the foliar spray of growth regulators consisting of salicylic acid, jasmonic acid, brassinosteroid and distilled water as control. Data variance analysis for different traits was done using SAS statistical software version 9.1.Results and DiscussionIn the row inter-cropping of 25% chickpeas + 75% barley, compared to the monocropping of these two plants the leaf sodium concentration of chickpeas and barley showed a decrease of 5 and 3%, respectively. An increase in leaf nitrogen concentration was observed in the mixed cropping of chickpeas and barley compared to the monocropping system. In the monocropping of chickpeas and barley, salicylic acid and jasmonic acid foliar application improved the leaf potassium content of chickpeas and barley. In the conditions of mixed cropping, foliar spray of salicylic acid and jasmonic was able to increase the leaf potassium concentration of chickpeas compared to the control. The plant's ability to remove sodium from the cytosol increases water absorption and preserves photosynthetic pigments. The results of this experiment confirmed the hypothesis of synergistic effects of row inter-cropping compared to monocropping. Positive changes in the row inter-cropping can be related to the diverse absorption of ions by plants, changes in ion solubility and interaction between ions. In 2021, the highest biological yields of chickpeas and barley (3199 and 10351 kg ha-1) were observed in mixed cropping of 50% chickpeas + 50% barley. In 2022, the row inter-cropping of 50% chickpeas + 50% barley increased the biological yield of chickpeas and barley by 9% and 18%, respectively, compared to monocropping. The highest yield of chickpeas and barley seeds was observed in row inter-cropping of 75% chickpea + 25% barley, using foliar spray of salicylic acid and jasmonic acid. The increase in the grain yield of chickpeas and barley plants in other treatments of row inter-cropping was also observed with foliar spray of salicylic acid and jasmonic acid. ConclusionThe results of this research showed that salt stress and sodium absorption cause disturbances in the absorption of nutrients. Foliar spray of growth regulators improved growth by reducing sodium and increasing nutrient absorption. Also, the positive effect of row inter-cropping of chickpeas and barley compared to their monocropping on increasing the growth and grain yield under salt stress conditions was a successful result. Therefore, row inter-cropping can be used to ensure production stability under salinity stress conditions.AcknowledgmentWe would like to thank the Fars Agricultural and Natural Resources Research and Education Center, AREEO, and the Islamic Azad University of Fasa for their sincere assistance in carrying out this research..